2010
DOI: 10.1002/adfm.200901684
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Control of Linear‐Shaped Molecules in Vacuum‐Deposited Organic Amorphous Films and Its Effect on Carrier Mobilities

Abstract: The molecular orientation of linear‐shaped molecules in organic amorphous films is demonstrated to be controllable by the substrate temperature. It is also shown that the molecular orientation affects the charge‐transport characteristics of the films. Although linear‐shaped 4,4′‐bis[(N‐carbazole)styryl]biphenyl molecules deposited on substrates at room temperature are horizontally oriented in amorphous films, their orientation when deposited on heated substrates with smooth surfaces becomes more random as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
216
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 157 publications
(234 citation statements)
references
References 19 publications
8
216
4
Order By: Relevance
“…Thus, the decrease in absorbance reflects the randomization of molecular orientation. 17) In contrast to the considerable changes in the absorbances of the vacuum-deposited films, those of the spincoated films were nearly unchanged after annealing. This result directly demonstrates that the molecular orientations in the as-prepared spin-coated films are nearly random similarly to those in the annealed spin-coated films.…”
mentioning
confidence: 97%
“…Thus, the decrease in absorbance reflects the randomization of molecular orientation. 17) In contrast to the considerable changes in the absorbances of the vacuum-deposited films, those of the spincoated films were nearly unchanged after annealing. This result directly demonstrates that the molecular orientations in the as-prepared spin-coated films are nearly random similarly to those in the annealed spin-coated films.…”
mentioning
confidence: 97%
“…This result is very promising for using these materials for phosphorescent OLEDs [10] and as donor materials for organic solar cells. [29][30][31][32] Experimental Section X-ray data for Ir1a:C 85 H 95 F 8 .Phasenomenclature: Cr = crystal, SmA = smectic Am esophase, Iso = isotropic liquid. .C CDC 1418808 contains the supplementary crystallographic data for this paper.T hese data are providedf ree of charge by The Cambridge Crystallographic Data Centre.…”
mentioning
confidence: 99%
“…There has been considerable recent interest in controlling molecular orientation in organic semiconducting glasses (1)(2)(3)(4)(5)(6)(7). Whereas one might expect all glasses to be isotropic because of their structural disorder, Yokoyama et al and other groups have shown that molecular orientation in vapor-deposited glasses can be quite anisotropic (3,4,8,9) and depend upon deposition conditions (3).…”
mentioning
confidence: 99%